Southern side of the Suswani Mata Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here are the modern mandapa (pillared hall) constructions of the Suswani Mata Temple mandapa from the south side. It is done keeping in mind the sacred Kera tree which is believed to be the spot of manifestation of Suswani Ma (the presiding deity of the temple).